Literature Review Efektivitas Terapi SEFT (Spiritual Emotional Freedom Technique) Terhadap Hipertensi Pada Lansia - Khoirun Nissa; Lilla Maria; Agnis Sabat Kristiana (PROFESSIONAL HEALTH JOURNAL, 2023)
Introduction: Elderly is someone who experiences the aging process, decreased physiological function of body organs and triggers the emergence of hypertension. The absence of the executives of hypertension treatment in the old has brought about the disappointment of pharmacological administration of hypertension, so correlative treatment is expected to diminish circulatory strain, specifically SEFT treatment. The reason for this study was to decide the viability of SEFT treatment against hypertension in the old. Methods: The strategy utilized is a literature review. Results: The outcomes showed that 11 articles expressed that there was a decline in systolic and diastolic pulse utilizing SEFT treatment and 3 of them utilized a mix with different strategies. Conclusion: In this review, it tends to be reasoned that SEFT treatment is successfully completed freely by the old or helped by a friend. However, in carrying out this therapy, it must still be accompanied by pharmacological treatment according to the doctor's prescription and recommendation because it is to help treat, overcome, and stabilize hypertension in the elderly. Keywords: Elderly, Hypertension, Spiritual Emotional Freedom Technique